Development of the Institution of Administrative-Territorial Structure of the Russian Federation - Belyavskiy, Dmitriy; Mukhachev, Igor; Tereshchenko, Nikolay; Pogozheva, Olga; Strutinskaya, Tatyana; Avanesova, Anna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of this article is to investigate the problems of the administrative-territorial structure of the Russian Federation. The study reviews the work of leading researchers in the field of constitutional law and deals with regional aspects of the problem based on the example of the Stavropol Territory. The research method used is a qualitative research method by adopting a comprehensive research approach to investigate challenges related to the administrative-territorial structure in Russia, with a special focus on the Stavropa Region. The results of the study indicate that adequate federal legal requirements regarding the status of Caucasus Mineral Water have not been provided.